Ecological-safe and low-cost activated-bleaching earth: Preparation, characteristics, bleaching performance, and scale-up production. (10th January 2021) - Soetaredjo, Felycia Edi; Laysandra, Livy; Putro, Jindrayani Nyoo; Santoso, Shella Permatasari; Angkawijaya, Artik Elisa; Yuliana, Maria; Ju, Yi-Hsu; Zhou, Chun-Hui; Ismadji, Suryadi
Abstract: A high acidity extent, as a result of the activation process of bleaching earth, is a major drawback in the production of bleached-palm oil. The high acidity of bleaching earth generates problems for the process equipment as well as the product, which are economically disadvantageous. Addressing this pivotal issue in the manufacture, a more environmentally friendly and efficient activation process of bleaching earth using thermal activation is evaluated. Two types of bentonite-bleaching earth collected from two different locations were used throughout this study; that is from Pacitan and Ponorogo, coded as GS and SS, respectively. The effect of the proportion ratio of GS to SS (1:4, 2:3, 3:2, and 4:1), and variations in thermal activation temperature (150, 250, and 350 °C), to the bleaching performance were investigated. Thermal-activation at 150 °C can efficiently activate the bleaching earth without significant cation exchange capacity decrement. The pilot-scale bleaching process demonstrated that the prepared bleaching earth with GS to SS ratio of 3:2 (coded as M-03) could remove 96% of β-carotene from crude palm oil; which is the best among the investigated samples and also higher than the commercial bleaching earth (only 85–90% β-carotene removal). The feasibility of the production of M-03 at the industrial scale was analyzed by scaling up on the pilot scale. M-03 was able to be produced on an industrial scale by using a fluidized-bed dryer; this result has been adapted by a bleaching earth producing factory located in Madiun, Indonesia. Economic analysis on the factory demonstrated a payout time of 2 years and 10 months and the breakeven point of 21.5%. This paper shows the success of bringing the experimental results in laboratory-scale into the industrial-scale production of bleaching earth. Graphical abstract: Image 1